2022
DOI: 10.1097/bpo.0000000000002134
|View full text |Cite
|
Sign up to set email alerts
|

What is New in Pediatric Orthopaedic Foot and Ankle

Abstract: Background: This paper aims to report on the last 5 years of relevant research on pediatric foot and ankle pathology with specific focus on clubfoot, congenital vertical talus, toe walking, tarsal coalitions, pes planovalgus with or without accessory navicular, foot and ankle trauma, and talar dome osteochondritis dessicans. Methods: The Browzine platform was used to review the table of contents for all papers published in the following target journals related to the treatment of pediatric foot and ankle con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…Other authors have reported positive results with conservative treatment in isolated cases of CVT [1]. A critical review addressed the efficacy of conservative treatments for the flexible flat foot in children [2]. Conservative treatment of the flat foot in children has mainly involved in-shoe foot orthoses and orthopaedic footwear for the flexible flat foot.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have reported positive results with conservative treatment in isolated cases of CVT [1]. A critical review addressed the efficacy of conservative treatments for the flexible flat foot in children [2]. Conservative treatment of the flat foot in children has mainly involved in-shoe foot orthoses and orthopaedic footwear for the flexible flat foot.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment of the flat foot in children has mainly involved in-shoe foot orthoses and orthopaedic footwear for the flexible flat foot. Exercise for flat feet has also been described, but in the form of barefoot time and prescribed activities [2,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children > 6 years of age require an open osteotomy of the medial cuneiform or the base of the first metatarsal, followed by an osteotomy of the second through the four metatarsals. 32 33…”
Section: Metatarsus Adductusmentioning
confidence: 99%
“…31 Treatment in newborns is usually conservative, based on physical therapy, with casting and splints applied to the leg an open osteotomy of the medial cuneiform or the base of the first metatarsal, followed by an osteotomy of the second through the four metatarsals. 32,33 Flatfoot Deformity Flatfoot deformity is a complex and variable deformity that clinically includes exaggerated plantarflexion of the talus, subtalar eversion during weight-bearing, and a combination of valgus, external rotation, and dorsiflexion of the calcaneus relative to the talar head. The navicular bone becomes abducted and dorsiflexed relative to the talar head, drawing the entire midfoot and forefoot into abduction and supination relative to the hindfoot.…”
Section: Skewfootmentioning
confidence: 99%